Bioenergy in Southern Africa: An opportunity for regional integration? - Arndt, Channing; Henley, Giles; Hartley, Faaiqa (Informa UK Limited, 2019)
This introductory paper sets out the rationale for revisiting questions surrounding biofuel futures in Southern Africa and exploring the case for the establishment of a regional market. This contrasts with most research that has focused upon benefits and risks of production and consumption for individual countries. The analysis in this issue suggests that while benefits exist, the key challenges that have stifled production and consumption to date would need to be overcome. Unlocking trade requires relaxing requirements for South African manufacturers to source all their feedstock domestically. Key among factors to encourage production is resolving agricultural investment processes, particularly designing inclusive business models and clarifying land acquisition processes.